Portuguese Children's Sleep Habits Questionnaire -validation and cross-cultural comparison - Filipe Gloria Silva; Claudia Rocha Silva; Ligia Barbosa Braga; Ana Serrao Neto (Elsevier, 2014)
OBJECTIVE: To validate the Portuguese version of the Children's Sleep Habits Questionnaire (CSHQ-PT) and compare it to the versions from other countries. METHODS: The questionnaire was previously adapted to the Portuguese language according to international guidelines. 500 questionnaires were delivered to the parents of a Portuguese community sample of children aged 2 to 10 years old. 370 (74%) valid questionnaires were obtained, 55 children met exclusion criteria and 315 entered in the validation study. RESULTS: The CSHQ-PT internal consistency (Cronbach's α) was 0.78 for the total scale and ranged from 0.44 to 0.74 for subscales. The test-retest reliability for subscales (Pearson's cor-relations, n=58) ranged from 0.59 to 0.85. Our data did not adjust to the original 8 domains structure in Confirmatory Factor Analysis but the Exploratory Factor Analysis extracted 5 factors that have correspondence to CSHQ subscales. CONCLUSION: The CSHQ-PT evidenced psychometric properties that are comparable to the versions from other countries and adequate for the screening of sleep disturbances in children from 2 to 10 years old.